Affect Analysis In Top 5 UNICEF Instagram Palestine Posts - Heriyanto, Shayna Nelia Sevanka (LingPoet: Journal of Linguistics and Literary Research, 2025)
Affect in the appraisal framework is used as a model to examine the attitude and emotion expressed by the writer or speaker in the sentence context. This study aims to assess the affect on the 5 content with the most likes, in the form of photos and videos (reels), on the UNICEF Instagram in October 2024 with the topic of Palestine. A descriptive qualitative approach was used in writing this article. It has been found that UNICEF uses 25 affects and is more likely to use negative affects to depict the conflict in Palestine with the occurrence of 20 negative affects. In addition, UNICEF uses 3 positive affects and 2 neutral affects in Palestine-related content on Instagram.